Facebook usage and its association with psychological well-being among Malaysian adolescents - Naeemi, Somayyeh; Tamam, Ezhar; Hassan, Salleh; Bolong, Jusang (Elsevier, 2014)
Previous studies investigated possible effects of Facebook mostly on hedonic well-being but not focusing on individuals fully function of psychological well-being. This study tries to fill the gap by using Ryffs’ scale of psychological well-being. The respondents of this study were 401 adolescents aged between 13-16 years old, internet user, who lived in Selangor, Malaysia. Structural Equation Modelling was used to analyse the data. The results revealed that connectivity and organizing events on Facebook had a positive association with psychological well-being and information seeking has negative association with psychological well-being. This study offers two determinant factors on Facebook usage that can predict adolescents’ psychological well-being in Malaysian cultural context.